The RV camping framework for understanding modern camping practices. (July 2022) - Caldicott, Rodney W.; Scherrer, Pascal; Harris, Alana
Abstract: Rapid growth of recreational vehicle (RV)-based camping is challenging traditional models centred on caravan park stays. Self-contained RV technology and social change facilitate stays outside of regulated commercial caravan park environments, shifting use into unregulated contexts. This disruption fuels heated stakeholder and political discourse in local to national jurisdictions. A current lack of conceptual clarity around camping allows ideological differences to dominate such discourse and conceals significant changes in practice. The RV camping framework purposely addresses this by providing conceptual clarity and facilitating semantic transparency to mitigate camping's growing complexity. Centred on the mobilities paradigm, it embeds the theories of panoptic gaze, recreation specialisation and networked sociality to explain RV camping's temporal, spatial and social dimensions. The four practice-based pre-trip and in-trip determinants and two key environments reveal relevant traits and indicators for a holistic consideration of the phenomenon. The framework provides a foundational reference for future discourse and study of the RV camping phenomenon. Highlights: Modern RV camping practice challenges traditional caravanning production and consumption models premised on caravan park stays. Stakeholder ideological difference dominates discourse concealing rapid change in RV camping practice observable through a spectrum of commercial, freedom, and multi-modal campers. The RV camping framework supports evidence-based and semantic transparency to further academic and practitioner discourse and research.